2022
DOI: 10.3390/antiox11040606
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Inflammatory Status in COVID-19 Outpatients: A Health Center-Based Analytical Cross-Sectional Study

Abstract: The antioxidant system can be critical in reducing exacerbated inflammation in COVID-19. This study compared the antioxidant and inflammatory responses between COVID-19 outpatients and seemingly healthy individuals. This descriptive-analytical cross-sectional study was conducted on 53 COVID-19 outpatients and 53 healthy individuals as controls. The serum concentrations of amyloid A (SAA), total antioxidant capacity (TAC), superoxide dismutase (SOD), and glutathione peroxidase (GPx) were measured and compared b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 48 publications
2
13
0
1
Order By: Relevance
“…The value of selenium upon glutathione peroxidase 1 activity and oxidative stress mitigation in SARS-CoV-2 infection and COVID-19 disease has been clearly emphasized recently ( Seale et al, 2020 ; Fakhrolmobasheri et al, 2021 ) and can prevent atherosclerosis progression in SARS-CoV-2 infection. The recent demonstration of elevated superoxide dismutase, GSH peroxidase, and total antioxidant capacity in COVID-19 outpatients compared to controls could be interpreted as a response to excessive COVID-19-related oxidative stress ( Golabi et al, 2022 ). Adequate levels and function of GSH and selenoproteins can prevent worsening of acute respiratory distress syndrome and atherosclerosis, two main causes of morbimortality in SARS-CoV-2 infection and COVID-19 disease.…”
Section: Sars-cov-2 New Therapeutic Approachesmentioning
confidence: 99%
“…The value of selenium upon glutathione peroxidase 1 activity and oxidative stress mitigation in SARS-CoV-2 infection and COVID-19 disease has been clearly emphasized recently ( Seale et al, 2020 ; Fakhrolmobasheri et al, 2021 ) and can prevent atherosclerosis progression in SARS-CoV-2 infection. The recent demonstration of elevated superoxide dismutase, GSH peroxidase, and total antioxidant capacity in COVID-19 outpatients compared to controls could be interpreted as a response to excessive COVID-19-related oxidative stress ( Golabi et al, 2022 ). Adequate levels and function of GSH and selenoproteins can prevent worsening of acute respiratory distress syndrome and atherosclerosis, two main causes of morbimortality in SARS-CoV-2 infection and COVID-19 disease.…”
Section: Sars-cov-2 New Therapeutic Approachesmentioning
confidence: 99%
“…16,17 In this scenario, adequate intake of nutrients is essential for an optimal immune response able to prevent infections, and to counteract inflammatory state and oxidative stress, strengthening a relationship between nutrition and individual response to disease burden. 18,19 Consistent with this concept, a recent cross-sectional study showed the importance of adequate levels of vitamin D and zinc for their immunomodulatory and direct antiviral effects during SARS-CoV-2 infection. Similarly, these nutrients are noteworthily required for normal skeletal growth and bone homeostasis, 20,21 further supporting their adequate intake during COVID-19 to prevent bone loss.…”
Section: Introductionmentioning
confidence: 84%
“…Furthermore, the virus also targets and disrupts the body's antioxidant defense mechanisms, leading to an even greater increase in oxidative stress. Therefore, managing oxidative stress may be an important therapeutic strategy for COVID-19 treatment, and antioxidants such as vitamin C and N-acetylcysteine have been studied for their potential benefits in this regard (34).…”
Section: The Role Of Oxidative Stress In Cancer and Covid-19mentioning
confidence: 99%